Digital Financial Literacy and Adoption of Digital Financial Services: Evidence from Kathmandu Valley (Quest Journal of Management and Social Sciences, 2026)
Background: The growth of digital technologies has increased the use of digital financial services such as mobile banking and online payments in Kathmandu Valley. However, effective use of these services depends on individuals’ digital financial literacy. Limited awareness of digital financial products, risks, and consumer rights highlights the need to understand factors influencing digital financial literacy and service usage.Purpose: The purpose of the study is to analyze the factors affecting digital financial literacy and usage of digital financial services among individuals within Kathmandu valley. Despite the increasing popularity of digital financial transactions in the Kathmandu valley, there is little research on how individual usage of digital financial services is impacted by digital financial literacy.Design/methodology /approach: Explanatory research design is used in this study. 420 respondents were selected through non-probability convince sampling technique. Partial least square structural equation modeling was used to analyze the data. The main theory used in this study is UTAUT to show dependent and independent variables relations. To examine the data both descriptive and inferential statistics were used. Self-administered questionnaires are used to ask opinion of respondents. Kobo toolbox is used for data collection.Findings: In the study, more respondents are married than unmarried participators with tertiary education that used digital financial products and services in the Kathmandu valley participated. The biggest problem identified by respondents was the cost of digital financial services, which needs to be adjusted, and the need for consumer education.Conclusion: This study shows that people's comprehension of consumer rights in digital financial transactions, awareness of digital financial risks and how to manage them, and familiarity with digital financial products and services all play significant roles in encouraging financial well-being and decision-making. To improve people's digital financial literacy, the report underlines the necessity for specialized educational programs, expanded awareness campaigns, and efficient consumer protection laws.Keywords: Digital financial literacy, financial services, consumer rights, financial risks